The Contribution of Beef Cattle Productivity to Regional Economic Development: An Analysis of the Effects of Feed Availability and Pellet Feed on Food Security - Moh. Zaini; Salim Abd. (Jurnal Ekonomi Pembangunan, 2025)
The high dependence on beef imports, despite the increase in domestic production, highlights the urgency of strengthening the beef cattle subsector to enhance food security and regional economic development. This study aims to analyze the contribution of beef cattle productivity to regional economic development by examining the effects of feed availability and pellet feed on productivity, food security, and regional development in Madura Island. A quantitative approach was employed using Structural Equation Modeling-Partial Least Squares (SEM-PLS) with data collected from 400 beef cattle farmers across four districts. The findings reveal that feed availability significantly influences productivity but does not have a direct impact on regional economic development. In contrast, pellet feed plays a crucial role not only in improving productivity but also in exerting a strong direct effect on regional economic development. Beef cattle productivity is proven to be a key mediating variable that channels the influence of feed inputs on both food security and regional development. These results underscore the importance of policy strategies that balance forage management with the adoption of pellet feed technology to strengthen food security while simultaneously promoting sustainable regional economic development.